Smart protection scheme for microgrids with distributed energy resources - Panida Thararak (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The flexible operation of microgrids, along with the availability of distributed energy resources, causes a variety of changes in short-circuit current levels, magnitudes, and directions that have undesirable effects on the operation of protection systems. Conventional protection schemes use typical directional overcurrent relays with limited operating capability, unable to respond to microgrid operations in the manner of shortcircuit current changes. In this research, a novel quaternary protection scheme implemented with dual-directional overcurrent relays (dual-DOCRs) is developed to protect the short-circuit faults in microgrids, taking into account the interconnection of distributed generation units. The optimal dual-DOCR setting and coordination are formulated as an optimization problem solved by an evolutionary programming approach to minimize the total relay operating times. A centralized protection control strategy based on the smart grid concept is proposed to increase the adaptability of the dual-DOCRs, which have multiple relay setting groups in accordance with system state changes. The simulation case studies are performed using two benchmark IEEE test systems and a practical distribution system. Test scenarios, including the operations of microgrids, DGs availabilities, and different fault events are analyzed. The comparative studies with conventional protection schemes show that the quaternary scheme achieves the efficient coordination between the primary and backup relays, and increases the response-ability of the protection system, resulting in the enhancement of selectivity, sensitivity, and speed of microgrid protection systems.